Analisis Hukum Konflik Jual Beli Tanah Berdasarkan Surat Kuasa Mutlak tanpa Sepengetahuan Penjual : Studi Putusan Mahkamah Agung Nomor 680 K/Pdt/2020 - Malik Syaifuddin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article examines the validity of the sale and purchase of land rights based on an absolute power of attorney without the knowledge of the seller, focusing on Supreme Court Decision Number 680 K/Pdt/2020. This study aims to analyze the validity of the use of an absolute power of attorney in the process of transferring land rights and its legal implications. The results of the study indicate that the use of an absolute power of attorney in the transfer of land rights is contrary to the provisions of laws and regulations, especially Article 39 paragraph (1) letter d of Government Regulation Number 24 of 1997 concerning Land Registration. This absolute power of attorney is declared null and void by law because it contains elements of irrevocable transfer of rights, which is contrary to the principle of